2017
DOI: 10.1186/s13098-017-0296-z
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive diabetic patients: incidence of cardiovascular and renal outcomes in a historical cohort over 11 years

Abstract: BackgroundDiabetics have increased risks for cardiovascular disease (CVD) and mortality, reducing their life expectancy by up to 15 years. Type 2 diabetes mellitus specifically increases the risk for cardiovascular mortality nearly fivefold. When hypertension is combined with diabetes, the risk of CVD is even greater.ObjectiveIdentify non-fatal cardiovascular outcomes and renal function impairment in a cohort of hypertensive patients in regular treatment in a reference treatment center, over 11 years of follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“… 4 , 5 , 31 Hypertension-mediated organ damage represents the result of the direct and indirect effect of chronic pressure overload, intensified by the harmful impact of additional cardiovascular risk factors possibly coexisting, with a negative impact on cardiovascular prognosis. 32 Hypertension-mediated organ damage often clusters together, reflecting the extension of the hypertensive burden. 12 …”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 , 31 Hypertension-mediated organ damage represents the result of the direct and indirect effect of chronic pressure overload, intensified by the harmful impact of additional cardiovascular risk factors possibly coexisting, with a negative impact on cardiovascular prognosis. 32 Hypertension-mediated organ damage often clusters together, reflecting the extension of the hypertensive burden. 12 …”
Section: Discussionmentioning
confidence: 99%
“…Given the positive results of the present study and previous studies involving patients from the same HTN treatment center, 14,16,17,33,34 the format adopted in our service can be a model for other centers handling patients diagnosed with HTN and aiming to implement a team-based strategy.…”
Section: Discussionmentioning
confidence: 73%
“…Although our multidisciplinary service has always focused on the overall patient management it is primarily specialized in hypertension treatment, which can explain this finding. Previous studies conducted in the same setting also showed good results in blood pressure management [ 11 , 21 ] which must be simultaneously seen as extremely positive and as a call for action to improve management of other co-morbidities.…”
Section: Discussionmentioning
confidence: 91%